The Impact of Norwegian Labor Market Policy on Disability Employment - Ulstein, Julie (Nordic Journal of Working Life Studies, 2025)
Despite generous welfare systems and relatively high employment rates, sizable employment gaps persist in the Nordic countries between people with disabilities and the general population. Evaluations of previous policies can be important tools for designing and implementing more effective ones. This study contributes to this objective by analyzing the impact of a Norwegian policy, the ‘joint inclusion effort’, on the labor market participation of people with disabilities. Using registry data from 2015 to 2021 and a difference-in-differences design, the study estimates the effect of this policy on the probability of employment for people with disabilities. The findings suggest a small positive effect of the policy on overall labor market participation. The results prompt a discussion on the implications for active labor market policy and directions for future research.